2013
DOI: 10.1590/s0103-05822013000300004
|View full text |Cite
|
Sign up to set email alerts
|

Craniofacial abnormalities among patients with Edwards Syndrome

Abstract: OBJECTIVE To determine the frequency and types of craniofacial abnormalities observed in patients with trisomy 18 or Edwards syndrome (ES). METHODS This descriptive and retrospective study of a case series included all patients diagnosed with ES in a Clinical Genetics Service of a reference hospital in Southern Brazil from 1975 to 2008. The results of the karyotypic analysis, along with clinical data, were collected from medical records. RESULTS: The sample consisted of 50 patients, of which 66% were female. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Two pedonculated skin tags were found anterior to the left ear in a 2‐month‐old female [Smith et al, ]. A recent study reported preauricular tags, which are usually considered as malformative benign tumors, in 10% of children with trisomy 18 [Rosa et al, ]. A red pedonculated hamartoma occupied the left cheek of a newborn girl who later developed hepatoblastomas [Kitanovski et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…Two pedonculated skin tags were found anterior to the left ear in a 2‐month‐old female [Smith et al, ]. A recent study reported preauricular tags, which are usually considered as malformative benign tumors, in 10% of children with trisomy 18 [Rosa et al, ]. A red pedonculated hamartoma occupied the left cheek of a newborn girl who later developed hepatoblastomas [Kitanovski et al, ].…”
Section: Resultsmentioning
confidence: 99%
“…The most frequently affected systems in trisomy 18 were the craniofacial, anomalies of the extremities, cardiac, respiratory, central nervous system, genitourinary, and, to a lesser extent thorax, abdomen, and intestine (Rosa et al ., 2013a; Rosa et al, 2013b). However, limited studies on fetuses with trisomy 18 are available in the literature from a perinatal cohort except for the one report describing five fetuses with trisomy 18 following autopsy (Sandal et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The risk of recurrence of trisomy 18 in a family with an affected child is 1% (Fick and Sexson Tejtel, 2021). Diagnoses at the prenatal period were based on screening by maternal age and maternal serum markers, ultrasonography, and cytogenetic studies followed by chorionic villi sampling or amniocentesis (Rosa et al ., 2013a; Rosa et al, 2013b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The very minor and focal cranial shape changes seen with bathrocephaly have no known medical or neurocognitive consequences, 30 yet the phenotype should be distinguished from other conditions with a prominent occiput such as sagittal craniosynostosis, Edwards syndrome (>50%), and Beckwith-Wiedemann syndrome (72%). 31 , 32 Fortunately, most cases of bathrocephaly can be diagnosed with clinical examination (isolated occipital projection with no other cranial shape changes and a palpable transverse ridge across the occiput) and do not require a confirmatory CT scan.…”
Section: Discussionmentioning
confidence: 99%